Understanding telehealth mediated cancer care in Northern BC First Nations communities: health professionals’ perspectives - Sidhu, Jatinderpal (2012)
Objective The use of telehealth to provide health service delivery to rural and remote First Nations populations Canada-wide has greatly increased in recent years. Telehealth provides a mechanism for these disadvantaged and underserved communities to access timely healthcare services that would otherwise be expensive, delayed or unavailable due to geographic and resource limitations. There are numerous benefits, challenges and cultural issues that must be understood from a healthcare professional perspective when providing telehealth care to First Nations communities. Once educated with respect to these issues and experienced in providing care, healthcare professionals are well poised to provide feedback with respect to improving telehealth mediated health care delivery. This thesis examines these issues in the context of using telehealth for patient care, specifically cancer care. Methods This thesis is divided into two phases. Phase one is a literature review assessing the use of telehealth, specifically in rural and remote First Nations communities in Canada. Phase 2 is a study using a survey to assess healthcare professionals who provide telelehealth mediated patient care (in particular cancer care) to Northern BC First Nations communities. The participants were contacted through the use of an online survey tool to assess their perceptions of benefits, challenges, and cultural awareness when providing patient care. The survey population consisted of onsite health professionals and urban health professionals providing patient care to Northern BC First Nations communities via telehealth. Specific participant groups of interest were (1) onsite cancer care professionals, (2) onsite other (non-cancer) care professionals, (3) urban cancer care professionals, and (4) urban other (non-cancer) care professionals. Results The participant population of 45 was too limited a sample size for inferential statistics to be conducted. Therefore our survey data was interpreted by comparing the mean composite scores of the ...